An Electrolyte‐Free Flexible Electrochromic Device Using Electrostatically Strong Graphene Quantum Dot–Viologen Nanocomposites. (2nd June 2014) - Hwang, Eunhee; Seo, Sohyeon; Bak, Sora; Lee, Hanleem; Min, Misook; Lee, Hyoyoung
<x xml:space="preserve">Abstract</x> A strong electrostatic MV2+‐GQD nanocomposite provides an electrolyte‐free flexible electrochromic device wih high durability. The positively charged MV2+ and negatively charged GQD are strongly stabilized by non‐covalent intermolecular forces (e.g., electrostatic interactions, π–π stacking interactions, and cation‐π electron interactions), eliminating the need for an electrolyte. An electrolyte‐free flexible electrochromic device fabricated from the GQD‐supported MV2+ exhibits stable performance under mechanical and thermal stresses. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>